Lumican expression, localization and antitumor activity in prostate cancer - Coulson-Thomas, Vivien J. (2013)
The stromal reaction surrounding tumors leads to the formation of a tumor-specific microenvironment, which may play either a restrictive role or a supportive role in the growth and progression of the tumors. Lumican, a small leucine-rich proteoglycan (SLRP) of the extracellular matrix (ECM), regulates collagen fibrillogenesis. Recently, lumican has also been shown to regulate cell behavior during embryonic development, tissue repair and tumor progression. The role of lumican in cancer varies according to the type of tumor. In this study we analyze the role of lumican in the pathogenesis of prostate cancer both in vivo and in vitro. Overall lumican up-regulation was observed in the primary tumors analyzed through both real-time PCR and immunostaining. The increase in lumican expression was observed in the reactive stroma surrounding prostate primary tumors with fibrotic deposition surrounding the acinar glands. In vitro analysis demonstrated that lumican inhibited both the migration and invasion of metastatic prostate cancer cells isolated from lymph node, bone and brain. Moreover, prostate cancer cells seeded on lumican presented a decrease in the formation of cellular projections, lamellipodia detected by a decreased rearrangement in ZO-1, keratin 8/18, integrin β1 and MT1-MMP, and invadopodia detected by disruption of α-smooth muscle actin, cortactin and N-WASP. Moreover, a significant increase in prostate cancer cell invasion was observed through the peritoneum of lumican knockout mice, further demonstrating the restrictive role lumican present in the ECM has on prostate cancer invasion. In conclusion, lumican present in the reactive stroma surrounding prostate primary tumors plays a restrictive role on cancer progression, and we therefore postulate that lumican could be a valuable marker in prostate cancer staging.